Notions of Music in the Training of Music Therapists: Analysis of Academic Programs, University of Buenos Aires, Argentina - Revuelta Berlanga, Juan; Tosto, Virginia; Vazquez, Maria Florencia (Voices: A World Forum for Music Therapy, 2025)
As in the rest of Latin America, music therapy training programs in Argentina seem to follow guidelines formulated in Europe and the United States, where teaching-learning strategies based on the conservatory model prevail. Our team investigated the characteristics of this model that are present in the academic training of music therapy graduates who studied at the University of Buenos Aires in 2022. Through a qualitative research process, the syllabi of all subjects were analyzed (using Atlas.ti 8), exceptfor the References section. The results showed that in the training offered by the University, music is considered an expressive modality, that improvisation is the musical experience most valued by teachers, and that there is a strong interest in analyzing sound productions, either formally or informally. The musical instruments mentioned most frequently are percussion instruments and the voice. Decolonial thinking is critical of the Conservatory’s pedagogical model, which limits the processes of musical teaching and learning to reading and writing, and privileges instrumental performance. A critical review of the current curriculum in light of decolonial thinking could contribute to the construction of situated knowledge and allow work to be done, within the degree program, on the effects of coloniality on the training of music therapists. Editorial Comment What ideas about music are conveyed in the academic training of future music therapists? Which aspects of this training are linked to Eurocentric pedagogical models and which can be understood from decolonial perspectives? We believe that the authors’concern to warn us about the importance of making visible the places from which the subjects and institutions involved make their statements and assign value to them is central. They tell us that, as trainers of music therapists in Latin America: “We can make explicit the place from which knowledge is produced, whether it is our own or that which we use to develop our research and/or the training processes in which we are involved. We can make explicit that the division between popular and academic music responds to prejudices linked to the place of origin of the music; we can include the music of indigenous peoples, folk music, popular music, and urban music in the repertoires of our subjects. We can recognize the processes of ‘whitening’of such music in the effort to bring it into academic circles.”